2021
DOI: 10.3390/ijerph18062893
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Experience, Perceived Match Importance, and Anxiety on Cortisol Response in an Official Esports Competition

Abstract: The aim of the present study was to analyse the neuroendocrine stress response, psychological anxiety response, and perceived match importance (PMI) between expert and non-expert control gamers in an official competitive context. We analyzed, in 25 expert esports players and 20 control participants, modifications in their somatic anxiety, cognitive anxiety, self-confidence, PMI, and cortisol in a League of Legends competition. We found how expert esports players presented higher cortisol concentrations (Z = 15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 43 publications
0
22
0
3
Order By: Relevance
“…The frontal lobe of the brain is highly involved with the processing of attention and executive functions, and arousal levels appear to facilitate such functions to a certain extent (1). Mendoza et al (17) examined a group of expert eSport gamers who participated in tournaments and a recreational control group of gamers who never played eSport games with real strategy demands. It might be suggested that higher skilled players partitioned in this study and in the study by Mendoza et al (17) would have greater perception of the oncoming game demands.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The frontal lobe of the brain is highly involved with the processing of attention and executive functions, and arousal levels appear to facilitate such functions to a certain extent (1). Mendoza et al (17) examined a group of expert eSport gamers who participated in tournaments and a recreational control group of gamers who never played eSport games with real strategy demands. It might be suggested that higher skilled players partitioned in this study and in the study by Mendoza et al (17) would have greater perception of the oncoming game demands.…”
Section: Discussionmentioning
confidence: 99%
“…Mendoza et al (17) examined a group of expert eSport gamers who participated in tournaments and a recreational control group of gamers who never played eSport games with real strategy demands. It might be suggested that higher skilled players partitioned in this study and in the study by Mendoza et al (17) would have greater perception of the oncoming game demands. This would lead to greater arousal and anxiety preparing players for more rapid neurophysiological adjustments before game play.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…La literatura científica indica que hay más factores estresantes e intensos durante la competición (p.ej., por el resultado, acción del rival y expectativas de triunfo) que durante los entrenamientos (Poulus et al, 2022) y cierto aumento de la ansiedad antes de la competición (Mendoza et al, 2021), mientras que los eventos que ocurren durante el juego (p.ej., bajo rendimiento, dificultades y errores), así como el resultado final (derrota), influyen negativamente en el estado de ánimo (Mateo-Orcajada et al, 2022). Además, existen ciertos factores estresantes que van más allá del propio videojuego, como puede ser la audiencia (fans) y dar respuesta a las redes sociales (Leis et al, 2022).…”
Section: Palavras-chaveunclassified
“…), así como practicar la desconexión digital (p.ej., al menos un día a la semana estar sin ningún dispositivo electrónico).En relación a las carreras duales, una alta dedicación tecnológica puede generar cierta interferencia y dificultad de compaginar ambas actividades por falta de tiempo, fatiga mental o motivación, cuestión que se requiere atender y equilibrar(Himmelstein et al, 2017).En relación a las áreas de mejora individual, se cumple la hipótesis 3 (los gamers tendrán dificultades en la autogestión emocional). En concreto, los gamers perciben ansiedad ante la competición y baja tolerancia a la frustración, cuestiones que se señalaron en trabajos anteriores(Bányai et al, 2019;Bonilla et al, 2022;García-Naveira, 2019;Himmelstein et al, 2017;Leis y Lautenbach, 2020;Leis et al, 2022;Mateo-Orcajada et al, 2022;Mendoza et al, 2021;Poulus et al, 2022;Sabtan et al, 2022).Con los objetivos de potenciar el rendimiento y cuidar la salud mental de los gamers, se necesitan establecer ciertos factores protectores (delimitar horas de dedicación y hábitos saludables), desarrollar ciertas características personales (resiliencia, tolerancia a la frustración y habilidades de afrontamiento al estrés), potenciar los entrenamientos y generar una transferencia de lo entrenado a la competición (reducir la brecha de estrés y exigencia entre ambas situaciones), atender las situaciones pre-competitivas, competitivas y sus resultados, así como la gestión de los factores externos a los esports (redes sociales, streaming, etc. ).…”
unclassified